Assessing growth in occupational licensing of low-income occupations: 1993-2012. Issue 2 (9th July 2018) - Timmons, Edward; Meehan, Brian; Meehan, Andrew; Hazenstab, John
Abstract : Purpose: The purpose of this paper is to document the changes in low- and moderate-income occupational licensing over time. Design/methodology/approach: Using US state level data, the authors document the rise in occupational licensing for low- and moderate-income occupations over the 1993-2012 period. Findings: States averaged 32 additional low- and moderate-income occupations licensed over this period. Louisiana added the most licenses with 59 new licenses for these occupations, while Oklahoma and Kentucky only added 15 licenses for these low- and moderate-income occupations. Originality/value: These data have not been documented before and should provide useful for future research into occupational licensing.